The Influence of Diagnosis Intervention Packet Policy Intervention on Medication Structure and Drug Cost of Elderly Hypertensive Inpatients in China: A Multicenter Interrupted Time-Series Analysis - Hong D; Lv D; Wu J; Li X; Zhao Q; Lu X; Li L (Dove Medical Press, 2023)
Dongsheng Hong,1,2 Duo Lv,1 Jiaying Wu,1 Xin Li,1 Qingwei Zhao,1 Xiaoyang Lu,1 Lu Li2 1Key Laboratory for Drug Evaluation and Clinical Research of Zhejiang Province, the First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, People's Republic of China; 2Department of Social Medicine of school of Public Health, Zhejiang University School of Medicine, Hangzhou, People's Republic of ChinaCorrespondence: Xiaoyang Lu, Key Laboratory for Drug Evaluation and Clinical Research of Zhejiang Province, the First Affiliated Hospital, Zhejiang University School of Medicine, 79 Qingchun Road, Hangzhou, 310003, People's Republic of China, Email luxiaoyang@zju.edu.cn Lu Li, Department of Social Medicine of school of Public Health, Zhejiang University School of Medicine, 866 Yuhangtang Road, Hangzhou, 310058, People's Republic of China, Email lilu@zju.edu.cnBackground: DIP is a new medical insurance payment system developed in China which was implemented in Guangzhou in January 2018, but few studies have focused on its intervention effect on the drug burden of elderly hypertensive patients.Methods: Nine medical institutions in Guangzhou, China, were selected, among which, daily full medical orders of elderly hypertensive inpatients from 2016 to 2020 were randomly collected. To assess the impact of DIP policy intervention on patient drug burden, we took the data after policy implementation in January 2018, as the intervention data, and applied a segmented regression model with interrupted time series to analyze the trend and changes in average daily drug costs per month and medication structure, stratified by age, sex, and inpatient department.Results: A total of 34,276 elderly hypertensive patients' daily full medical orders were obtained. The immediate level change of drug costs after intervention was − 23.884 RMB/month (P = 0.652), and the trend change was statistically significant (− 15.642 RMB/month, P = 0.002). The relative cumulative effect at the end of the study was − 78.860% (95% CI: − 86.087% to − 69.076%), and the intervention effect was more significant in surgical and male patients. The analysis of drug structure changes showed that after the implementation of the DIP policy intervention, the proportion of anti-infective drugs, anti-tumor drugs, and biological products all showed a significant downward trend (P < 0.05), while nutritional drugs showed a significant upward trend (P = 0.011), but no immediate horizontal change in slope was observed.Conclusion: The typical practice in China showed that DIP policy intervention can improve the drug burden of elderly hypertensive hospitalized patients and has a stable long-term effect, and the intervention effect is not consistent across different clinical department and populations with different characteristics, and it would also cause changes in the medication structure.Keywords: diagnosis-intervention packet policy, daily drug cost, interrupted time series analysis, elderly hypertension, medication structure